Product Branding Education Impact Analysis on the Visual Identity of MSMEs in Pagesangan: Analisis Dampak Edukasi Branding Produk Terhadap Kemampuan Identitas Visual UMKM Kelurahan Pagesangan - Zahrah Hayat Arka Putri; Delia Putri Perpatih; Tatia Shafwa Sinatria; Rizky Salman Al Faysi; Tri Lathif Mardi Suryanto (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
The Thematic Community Service Program (KKNT) for defending the SDGs (Sustainable Development Goals) by Group 126 aims to increase the capacity of MSMEs in Pagesangan Village in building a strong visual identity through product branding education. This activity is motivated by the low understanding of MSMEs regarding the importance of visual elements such as logos, colors, typography, and packaging in forming a professional and competitive brand image. The program is implemented through several stages, namely simple financial management training, branding strategies, visual design practices in the form of a professional and competitive brand image, and evaluation of MSME social media. The program evaluation was carried out using the Kirkpatrick model covering four aspects, namely reactions, learning, behavior, and results. The results of the analysis showed a significant increase in participants' understanding and skills in applying branding elements consistently, as seen by a post-test score of 100% compared to the variation in scores in the pre-test. This branding education has proven effective in strengthening the competitiveness of MSME products and has become a sustainable SDGs-based empowerment model that is worthy of replication.